2014
DOI: 10.3109/13625187.2014.919379
|View full text |Cite
|
Sign up to set email alerts
|

A literature review on the relationship between infertility and sexual dysfunction: Does fun end with baby making?

Abstract: Appropriate measures should be designed to identify sexual disorders in infertile couples, and the medical team should be trained to deal systematically with the couple's sexuality and propose strategies to overcome sexual disturbances. This approach could preserve the quality of the couple's sexual relationship and maximise pregnancy chances in ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 25 publications
1
36
0
2
Order By: Relevance
“…Sexual dysfunction in men is correlated with sexual dysfunction in women (Nelson, Shindel, Naughton, Ohebshalom, & Mulhall, ). It has been postulated that clinicians should be trained to approach systematically to the couple's sexuality and produce strategies to deal with sexual problems (Piva, Lo Monte, Graziano, & Marci, ). It is very important that the couple is perceived as a whole and approached in such a way.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dysfunction in men is correlated with sexual dysfunction in women (Nelson, Shindel, Naughton, Ohebshalom, & Mulhall, ). It has been postulated that clinicians should be trained to approach systematically to the couple's sexuality and produce strategies to deal with sexual problems (Piva, Lo Monte, Graziano, & Marci, ). It is very important that the couple is perceived as a whole and approached in such a way.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that infertility can have both desirable and undesirable outcomes (Greil, Slauson‐Blevins, & McQuillan, 2010; Verhaak et al, ). For example, among the deleterious effects of infertility on relationships, sex can lose its spontaneity and become more chore‐like rather than a source of pleasure or expression of intimacy within the relationship (Piva, Lo Monte, Graziano, & Marci, ; see also Glover, McLellan, & Weaver, ; Ozkan, Orhan, Aktas, & Coskuner, ). Conversely, infertility can lead to stronger couple relationships (Peterson, Pirritano, Block, & Schmidt, ; Wagner, Wrzus, Neyer, & Lang, ), especially among partners who approach infertility as a shared problem (Greil, ).…”
Section: Education and Awareness Of Reproduction And Infertility Treamentioning
confidence: 99%
“…As most couples consider childbirth as one of the most significant outcomes of sexual intercourse, infertile couples are more prone to experience psychological and emotional stress [10]. Infertility profoundly impacts the sexual enjoyment of a couple about scheduling programs for childbirth and fertility interventions [11,12]. It has been shown that infertile couples have significantly more sexual issues than fertile couples [13].…”
Section: Introductionmentioning
confidence: 99%